2019
DOI: 10.1111/jfpe.13339
|View full text |Cite
|
Sign up to set email alerts
|

Extract‐rich in flavonoids from Hibiscus sabdariffa calyces: Optimizing microwave‐assisted extraction method and characterization through LC‐Q‐TOF‐MS analysis

Abstract: Hibiscus sabdariffa comprises calyx which is rich in flavonoids and numerous phytochemical compounds. Nevertheless, the extraction parameters can influence the recoveries of these bioactive compounds. It is then important to investigate the contributing effects of the process parameters and optimized their conditions to achieve higher recovery yield. Hence, this study was carried out to examine the contributing effects of microwave-assisted extraction (MAE) process factors (irradiation time, ethanol concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…The phenolic compounds (TPC and TFC) yield elevated from 240 to 331 mg GAE/g and 308 to 403 mg QE/g, respectively, as the power increased from 350 to 420 W and it is shown in Figures 2 and 3. This could be due to the improvement of power which leads to promote the solubility and diffusion of solute components out of the solid matrix (Alara, Abdurahman, Obanijesu, Alara, & Mudalip, 2020; Yingngam, Chiangsom, & Brantner, 2020). Moreover, the elevated pressure occurred due to microwaves inside the cell wall enhances micro explosions which could release the solute (Yingngam & Brantner, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The phenolic compounds (TPC and TFC) yield elevated from 240 to 331 mg GAE/g and 308 to 403 mg QE/g, respectively, as the power increased from 350 to 420 W and it is shown in Figures 2 and 3. This could be due to the improvement of power which leads to promote the solubility and diffusion of solute components out of the solid matrix (Alara, Abdurahman, Obanijesu, Alara, & Mudalip, 2020; Yingngam, Chiangsom, & Brantner, 2020). Moreover, the elevated pressure occurred due to microwaves inside the cell wall enhances micro explosions which could release the solute (Yingngam & Brantner, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Ethyl linoleate showed an anti-inflammatory effect by inducing the expression of HO-1 in RAW264.7 cells [59]. Apart from the compounds identified, previous reports using LC-MS analysis have also reported on the presence of various polyphenols with neuroprotective activities including luteolin, myricetin, kaempferol, quercetin, protocatechuic acid, and hibiscus acid [60,61].…”
Section: Discussionmentioning
confidence: 97%
“…Extraction involves separating dissolvable substances from non-dissolvable residues using solvent(s); it can be in form of liquid or solid [1]. There are two categories of extraction which are traditional and modern; the former includes Soxhlet, soaking, maceration, ultra-sonication, turbo-fast blending, and solvent permeation; the latter includes ultrasonic-assisted, subcritical, supercritical CO 2 , enzyme-assisted, pressure-assisted, and microwave-assisted methods [2][3][4][5][6]. The traditional methods are mainly associated with an extended time of extraction, destruction of heat-sensitive bioactive compounds, and enormous consumption of solvents [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the extraction time and microwave power fall within 30 s to 10 min and 25 to 750 W, respectively [17]. Several studies had reported the use of MAE for recovering phenolics from plant samples including bitter leaf, purple fleabane, roselle, tea leaf, vanilla, radix, flax seeds, scent leaf, siam weed, and among others [6,8,9,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%